Un fals aparegut en el «Tirant lo Blanch» - Mahiques Climent, Joan (Caplletra. Revista Internacional de Filologia, 2008)
In the chapters CCXXXI-CCXXXIIII of Tirant lo Blanc, there are two comical scenes where Carmesina and Tirant attempt to keep their love a secret. Carmesina justifies a night riot happened in her chamber by saying that a rat went through her face; whereas Tirant pretends to be a ghost when he runs away from the chamber into the orchard. The dependence of these two episodes opposes the nature of several characters, but the scene that best exhibits the knights’ ambivalent morality is the appearance of Tirant –with the spells of Hipòlit and the viscount of Branches. The comparison of this case with chapter XIX of the «Quixote», and with other works of the modern age, allows to determine how the forms and the meanings of a same commonplace evolve. The appearance of «Tirant» has to be linked especially to three mediaeval traditions: in the first place, the «fabliaux» and the «novelle», like the «Llibre de fra Bernat» or the «Decamerone»; in the second place, the treaties of ghosts, according to the outlines of «De spiritu Guidonis»; in the third place, the motif of the knightly adventure, in the way of Chrétien de Troyes. This is how Joanot Martorell balances and adapts diverse materials to the situations that the case brings up.